When something new comes to the countryside. About the development, implementation and diffusion of innovative and digital solutions for rural basic service provision - Mettenberger, Tobias; Zscherneck, Julia; Küpper, Patrick (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
For maintaining basic service provision in shrinking rural areas, great potential is attributed to digital solutions. At the same time, however, disadvantageous conditions for innovations are attested to such spaces, so that the realisation of novel approaches seems to be difficult, compared to agglomerations. In this context, a growing body of research examines the practice of those actors, who are responsible for local projects. In contrast, a much weaker focus lays on relationships with supra-regional key institutions and service providers, as well as on the related power structures. Given that need for research, we go further into the question which factors are influencing the development, implementation and diffusion of innovative and digital solutions for rural basic service provision. Our research is based on three regional case studies, two of them in the field of public health and one in thefield of schooling. Our problem-centred interviews and documentary research show key drivers in the dimensions of power, knowledge and space. Furthermore, we demonstrate a varying importance of key drivers and actor relations, dependent on the project phase. Besides the support of key institutions and mayor suppliers, the acceptance through local basic service providers is a decisive factor for effective implementation, everyday usage and potential special diffusion of the analysed digital solutions.
Keywords: Basic Services, Digitalisation, Rural Areas, Policy Mobilities, Innovations